2005
DOI: 10.1088/0957-4484/16/12/022
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and optical properties of ultra-thin zirconia films prepared by nitrogen-assisted reactive magnetron sputtering

et al.

Abstract: High-k ZrO2 films were prepared by nitrogen-assisted direct current reactive magnetron sputtering on n-type silicon (100). The microstructure and optical properties in relation to thermal budgets were investigated. X-ray photoelectron spectroscopy (XPS) was used to determine the chemical states. Atomic force microscopy (AFM) analysis indicated that the annealing temperature had significant effects on surface roughness. By using Fourier transform infrared spectroscopy (FTIR), the resistance to the interface gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…The results of the band gap energy are in agreement with the XRD results. The band gap value of the ZrO 2 obtained in the present work closely matches with earlier reports [11,22,23]. …”
Section: Resultssupporting
confidence: 92%
“…The results of the band gap energy are in agreement with the XRD results. The band gap value of the ZrO 2 obtained in the present work closely matches with earlier reports [11,22,23]. …”
Section: Resultssupporting
confidence: 92%
“…In recent years, zirconium dioxide (zirconia, ZrO 2 ) thin films, owing to excellent optical, thermal, mechanical and electrical properties [1][2][3][4][5][6][7][8][9][10], have been widely used in diverse fields, such as optical filters, anti-corrosion, protective and thermal barriers, gas sensor, anti-reflection coating [8,9] and as insulators in microelectronic devices [10]. Depending on deposition technique, its parameters and heat treatment, ZrO 2 films can exist in various phases, monoclinic, tetragonal, cubic and amorphous [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [11], Song et al and Zhu et al [12] found that the rms is approximately half of the surface roughness layer thickness in spectroscopic ellipsometry. In addition, the obtained values of the surface roughnesses are very small compared with the measured film thickness which are listed in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…The data of the crystalline structure was taken from Refs. [3,12]. of a-Be 3 N 2 thin films are surprisingly limited.…”
Section: Resultsmentioning
confidence: 99%